Visualization and suppression of interfacial recombination for high-efficiency large-area pin perovskite solar cells. (October 2018) - Stolterfoht, Martin; Wolff, Christian; Márquez, José; Zhang, Shanshan; Hages, Charles; Rothhardt, Daniel; Albrecht, Steve; Burn, Paul; Meredith, Paul; Unold, Thomas; Neher, Dieter
Abstract The performance of perovskite solar cells is predominantly limited by non-radiative recombination, either through trap-assisted recombination in the absorber layer or via minority carrier recombination at the perovskite/transport layer interfaces. Here, we use transient and absolute photoluminescence imaging to visualize all non-radiative recombination pathways in planar pin- type perovskite solar cells with undoped organic charge transport layers. We find significant quasi-Fermi-level splitting losses (135 meV) in the perovskite bulk, whereas interfacial recombination results in an additional free energy loss of 80 meV at each individual interface, which limits the open-circuit voltage (V OC ) of the complete cell to ~1.12 V. Inserting ultrathin interlayers between the perovskite and transport layers leads to a substantial reduction of these interfacial losses at both the p and n contacts. Using this knowledge and approach, we demonstrate reproducible dopant-free 1 cm2 perovskite solar cells surpassing 20% efficiency (19.83% certified) with stabilized power output, a highV OC (1.17 V) and record fill factor (>81%). Non-radiative recombination is a critical limiting factor for perovskite solar cell performance. Stolterfoht et al. visualize the various recombination pathways in planar pin cells with photoluminescence imaging and use it to design improved solar cells with 1 cm2 areas and ~20% efficiency.